Planktonic foraminiferal biogeography in the Indian sector of the Southern Ocean: Contribution from CPR data. (April 2016) - Meilland, Julie; Fabri-Ruiz, Salomé; Koubbi, Philippe; Monaco, Claire Lo; Cotte, Cédric; Hosie, Graham W.; Sanchez, Sophie; Howa, Hélène
Abstract: Within the framework of the Scientific Committee on Antarctic Research (SCAR) Southern Ocean-Continuous Plankton Recorder (SO-CPR) Survey, the oceanic regions around Crozet and Kerguelen Islands were investigated in February–March 2013. Living planktonic Foraminifera (LPF) were collected in the upper mixed layer with a CPR along a 2160 nautical mile sea transect that crossed main hydrological fronts in the Indian sector of the Southern Ocean. In the SO-CPR database, mean total abundances of Foraminifera occurring during late austral summer are highly variable at an inter-annual scale, from 10 to 250 ind.m −3, representing 10–40% of the total zooplankton abundance, respectively. In the Southern Ocean, major inter-annual changes in zooplankton community structure were already reported. In this study, we describe the large scale distributional pattern of individual planktonic foraminiferal species living in near-surface waters of the Indian sector of the Southern Ocean, and we attempt to explain why major spatial variability in relative species abundances occurs during a late austral summer. In February–March 2013, LPF total abundances recorded between 42.86°S and 56.42°S ranged from 0 to a maximum of 258 ind.m −3 . In the Open Ocean Zone, the LPF community was composed of four major species ( Globigerinita uvula, Neogloboquadrina pachyderma, Neogloboquadrina incompta, Globigerina bulloides ). Generally, LPF total abundances are supposed to mirror primary production induced by hydrological fronts or induced by topography near Crozet and Kerguelen Islands. However, during late austral summer 2013, high foraminiferal abundances in the upper mixed layer did not always match the pattern of near-surface primary production (high Chl- a concentration areas delineated from satellite imagery). Low LPF standing stocks in late austral summer in the Southern Ocean contrasted with the presence of high densities of heavily silicified diatoms. This suggests that the late bloom production is not a suitable resource for planktonic Foraminifera. Consequently, LPF regional distribution in the upper mixed layer cannot be directly reconstructed from Chl- a concentration maps derived from satellite imagery. Knowledge of phytoplankton community composition is needed to understand the impact of primary production on foraminiferal population dynamics. Our results also emphasize that the polar/subpolar foraminiferal assemblages are characterized by high abundances of G. uvula in the iron-enriched waters surrounding the French Sub-Antarctic Islands. This species might react either to coastal or late summer production in high latitudes. Highlights: CPR provides large-scale high resolution sampling of LPF in the upper mixed layer. CPR data are semi-quantitative estimates consistent with plankton tow samplings. Impact of complex hydrography (islands, frontal zone..) on near-surface populations. Foraminiferal population dynamics is strongly affected by phytoplankton composition. Noteworthy high abundances of Globigerinita uvula in iron-enriched waters.